Histamine H3 Receptor: A Novel Therapeutic Target in Alcohol Dependence? - Panula, Pertti; Nuutinen, Saara; Vanhanen, Jenni; Mäki, Tiia (Frontiers in Systems Neuroscience, 2012)
The brain histaminergic system is one of the diffuse modulatory neurotransmitter systems which regulate neuronal activity in many brain areas. Studies on both rats and mice indicate that histamine H3 receptor antagonists decrease alcohol drinking in several models, like operant alcohol administration and drinking in the dark paradigm. Alcohol-induced place preference is also affected by these drugs. Moreover, mice lacking H3R do not drink alcohol like their wild type littermates, and they do not show alcohol-induced place preference. Although the mechanisms of these behaviors are still being investigated, we propose that H3R antagonists are promising candidates for use in human alcoholics, as these drugs are already tested for treatment of other disorders like narcolepsy and sleep disorders.